Penerapan Sistem Akuaponik (Budidaya Ikan Dalam Ember) untuk Pemenuhan Gizi Dalam Mencegah Stunting di Desa Gending Kabupaten Probolinggo - Dyah Ayu Perwitasari; Tatik Amani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Panca Marga Probolinggo, 2019)
Gending Village is a village located in Gending District, Probolinggo Regency, consisting of 4 Hamlets, 4 RWs, 13 RT. RT 09 area. Buyut Hamlet is one of the areas in the village of Gending, Gending District. The majority of RT 9 residents have livelihoods as farmers. The area of ​​Buyut Hamlet was once a center for catfish farming in the village of Gending, but is now beginning to be abandoned because of the existence of a small amount of feed. The adoption of the budikdamber as the development of the aquaponics system is expected to be able to foster community interest in conducting fish and vegetable cultivation in one place, so that the yields obtained are also abundant and meet the nutritional needs derived from fish and vegetables. One effort to redevelop the local potential in the form of catfish farming, needs to be done an action in the form of socialization. The socialization was carried out by conveying material about hydroponics and buddhambers, which was followed by housewives of RT 9 with the aim to be able to fill spare time and develop the ability of catfish culture that had previously been nurturing, but also as a form of utilization of house yards or narrow land to be efficient and profitable. The practice was carried out by demonstrating the buddhamber accompanied by lecturers and student teams, and handing over the assemblies of the buddambers along with vegetables and fish to one of the residents as a pilot. The results obtained from this program are an increase in knowledge and skills of partners about fish farming in a bucket (Budikdamber) as well as an increase in family food independence by utilizing home yards through the cultivation of vegetables and fish in one place. Keywords: Gending, Aquaponics, Budikdamber, Nutrition, Stunting